2015
DOI: 10.1007/s00705-015-2712-8
|View full text |Cite
|
Sign up to set email alerts
|

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo

Abstract: We previously reported that SIRT1, an NAD(+)-dependent deacetylase belonging to the class III histone deacetylases, enhances hepatitis virus B (HBV) replication by targeting the transcription factor AP-1. However, the potential antiviral effects of nicotinamide, a SIRT1 inhibitor, have not yet been explored. In this study, we show that nicotinamide exhibits potent anti-HBV activity with little cytotoxicity. Nicotinamide suppressed both HBV DNA replicative intermediates and 3.5-kb mRNA expression. Moreover, nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
0
33
1
Order By: Relevance
“…It is interesting that SIRT1 has been shown to play both pro-viral and anti-viral roles, depending on the type of virus. The SIRT1 inhibitor showed a suppressive effect on hepatitis B virus (HBV) replication [51,52], while the SIRT1 activator showed a suppressive effect on human T-cell leukemia virus type 1 (HTLV-1) [53] and MERS-CoV [54]. Han [55] found that SIRT1 inhibited viral RNA transcription and translation in enterovirus 71 (EV 71, a RNA virus)-infected human rhabdomyosarcoma (RD) cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that SIRT1 has been shown to play both pro-viral and anti-viral roles, depending on the type of virus. The SIRT1 inhibitor showed a suppressive effect on hepatitis B virus (HBV) replication [51,52], while the SIRT1 activator showed a suppressive effect on human T-cell leukemia virus type 1 (HTLV-1) [53] and MERS-CoV [54]. Han [55] found that SIRT1 inhibited viral RNA transcription and translation in enterovirus 71 (EV 71, a RNA virus)-infected human rhabdomyosarcoma (RD) cells.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between CC and APN, and GA and ACE2 were not included in our current analysis, mainly due to our strict rules for target screening. Through Venn analysis of targets from VCG Plus, silent mating type information regulation 2 homolog 1 (SIRT1) was found to only interact with GA. SIRT 1 belongs to the sirtuin family which contains seven proteins (SIRT1-7) that are class III NAD + -dependent histone deacetylases (HDACs) [51]. It is interesting that SIRT1 has been shown to play both pro-viral and anti-viral roles, depending on the type of virus.…”
Section: Discussionmentioning
confidence: 99%
“…Other ABC transporters (i.e., ABCA1 and ABCG1), which stimulate the cholesterol efflux [181], may also promote S1P enrichment of HDL-like lipoproteins [182,183]. More recently, it has been reported that ApoA-I promotes S1P release from endothelial cells via ABCA1 [184]. Despite this, the role of this transporter in plasma levels of S1P remains controversial.…”
Section: Atp-binding Cassette (Abc) Transportersmentioning
confidence: 99%
“…SIRT‐1 inducer resveratrol had been shown to influence the HBV replication . Recently, the inhibition of the SIRT‐1 has been reported to inhibit the HBV replication . Therefore, targeting SIRT‐1 expression in the HBV infected cells might have antiviral activity.…”
Section: Introductionmentioning
confidence: 99%